Impact of Corona Virus Pandemic Lockdown on Employee Commitment in Deposit Money Banks Staff in Ekiti State - Awolaja, Ayodeji. M. (Archives of Business Research, 2023)
The study examined the impact of the Corona-Virus Pandemic lockdown on Employee Commitment in deposit money banks in Ekiti State. This study was designed along the line of a descriptive survey. The population of staff strength of these banks is numbered to be 427. The 427 number of staff is relatively low compared to other state; nonetheless it may be unachievable if the researcher tends to sample all the registered banks. Still, the study cut across the entire population involving all members of staff of deposit money banks in Ado-Ekiti, Ekiti State. Regression analysis was carried out to analyze the data. The study revealed that employee commitment among members of staff of deposit money banks in Ekiti State is determined by different factors which include work schedule and workload reduction while slashes in salary and slow pace of sales insignificantly determine employee commitment of staff. The study recommended management of banks should ensure that employee workloads are well suited and incorporated in the management agenda as this will help to reduce turnover intentions. They should also ensure adequate organisation growth in respect to promotion, remuneration, training, financial and non-financial incentives to employees in order to enhance employee commitment in this sector